1997
DOI: 10.1037/0735-7036.111.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the nonagouti coat-color allele on behavior of deer mice (Peromyscus maniculatus): A comparison with Norway Rats (Rattus norvegicus).

Abstract: The agouti locus influences coat color by antagonizing melanocyte-stimulating hormone (MSH) at its receptor on pigment cells and may antagonize MSH in neural tissue. This study replicates work on rats to assess whether behavioral (neural) effects of the agouti locus are as similar across mammals as those on coat color. Handling, open-field, platform jump, and food-novelty tests were conducted on agouti and nonagouti deer mice (Peromyscus maniculatus) following protocols in C. A. Cottle and E. O. Price (1987). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Our findings of altered locomotor and social behavior in non-agouti mice are consistent with a causal role for the agouti gene in the strain differences previously reported between agouti and non-agouti animals (Cottle and Price, 1987; Hayssen, 1997; Yamamuro and Shiraishi, 2011). Previous attempts to identify agouti mRNA expression in the central nervous system failed (Vrieling et al, 1994; Millar et al, 1995) leaving open the mechanism by which agouti might modulate behavior.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of altered locomotor and social behavior in non-agouti mice are consistent with a causal role for the agouti gene in the strain differences previously reported between agouti and non-agouti animals (Cottle and Price, 1987; Hayssen, 1997; Yamamuro and Shiraishi, 2011). Previous attempts to identify agouti mRNA expression in the central nervous system failed (Vrieling et al, 1994; Millar et al, 1995) leaving open the mechanism by which agouti might modulate behavior.…”
Section: Discussionsupporting
confidence: 91%
“…Mutations that result in the ubiquitous overexpression of agouti lead to the widespread blockade of melanocortin receptor signaling (Furumura et al, 1996) demonstrating that agouti is a non-specific antagonist of melanocortin receptors. Behavioral geneticists have successfully used correlations between behavioral traits and external morphometric features to classify and identify genetically controlled traits and investigate pleiotropic phenotypes (Arcus and Kagan, 1995; Hayssen, 1997). Several investigators have noted that coat color in rodents is associated with differences in behavior, and studies on wild mice and rat strains reported differences in both escape and aggressive behavior between non-agouti and agouti animals (Cottle and Price, 1987; Hayssen, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations include direct selection for coat color variants by humans (e.g., Pielberg et al 2008) and removal of selective pressures for camouflage. It is further conceivable that coat color variation is a pleiotropic effect of alleles influencing other traits and particularly behavior, including the level of tameness (Keeler and King 1942;Cottle and Price 1987;Hayssen 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The melanocortin system has been suggested to account for pleiotropic effects on behavior and physiological traits in a variety of species (Cottle and Price 1987;Ducrest et al 2008;Hayssen 1997;Keeler 1942;Schmutz and Berryere 2007). However, it is important to note that PMEL17 , the causative gene for the lack of pigmentation in White Leghorn chickens, is not involved in melanogenesis and is not assumed to affect the melanin pathway directly.…”
Section: Discussionmentioning
confidence: 99%
“…Pigmentation is associated with behavior and stress responses in a variety of species, (reviewed by Ducrest et al 2008;Hayssen 1997;Kittilsen et al 2009;Loehr et al 2008). …”
Section: Introductionmentioning
confidence: 99%